A STUDY OF THE VIETNAMESE TRANSLATION OF ENGLISH NON – FINITE CLAUSES AND ITS APPLICATION IN VIETNAMESE ENGLISH TRANSLATION - M. Ed Phan Thị Bé (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aims at presenting the usage of non – finite clauses and helping Vietnamese learners of English identify as well as understand English non – finite clauses. In addition, we hope to provide teachers and students with knowledge of the translation of English non – finite clauses.